2015
DOI: 10.1371/journal.pone.0138807
|View full text |Cite
|
Sign up to set email alerts
|

Familial Dysautonomia (FD) Human Embryonic Stem Cell Derived PNS Neurons Reveal that Synaptic Vesicular and Neuronal Transport Genes Are Directly or Indirectly Affected by IKBKAP Downregulation

Abstract: A splicing mutation in the IKBKAP gene causes Familial Dysautonomia (FD), affecting the IKAP protein expression levels and proper development and function of the peripheral nervous system (PNS). Here we found new molecular insights for the IKAP role and the impact of the FD mutation in the human PNS lineage by using a novel and unique human embryonic stem cell (hESC) line homozygous to the FD mutation originated by pre implantation genetic diagnosis (PGD) analysis. We found that IKBKAP downregulation during PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…Moreover, IKAP was also shown to interact directly with the motor protein dynein, suggesting that IKAP may also be involved in intracellular transport (Abashidze et al , 2014). These initial findings were further corroborated by transcriptome analyses in neuronal differentiated FD-derived embryonic stem cells as well as in FD embryonic brains (Lefler et al , 2015). In particular, these analyses revealed that in FD-derived neurons and embryonic brains synaptic vesicular and neuronal transport genes are directly or indirectly affected by IKAP depletion (Lefler et al , 2015).…”
Section: Ikap Cellular Functions: Implications For Pns Deficitsmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, IKAP was also shown to interact directly with the motor protein dynein, suggesting that IKAP may also be involved in intracellular transport (Abashidze et al , 2014). These initial findings were further corroborated by transcriptome analyses in neuronal differentiated FD-derived embryonic stem cells as well as in FD embryonic brains (Lefler et al , 2015). In particular, these analyses revealed that in FD-derived neurons and embryonic brains synaptic vesicular and neuronal transport genes are directly or indirectly affected by IKAP depletion (Lefler et al , 2015).…”
Section: Ikap Cellular Functions: Implications For Pns Deficitsmentioning
confidence: 60%
“…These initial findings were further corroborated by transcriptome analyses in neuronal differentiated FD-derived embryonic stem cells as well as in FD embryonic brains (Lefler et al , 2015). In particular, these analyses revealed that in FD-derived neurons and embryonic brains synaptic vesicular and neuronal transport genes are directly or indirectly affected by IKAP depletion (Lefler et al , 2015). Significantly, among the five types of HSANs, FD (HSAN III), HSAN IV (caused by mutations in NGF receptor), and HSAN V (caused by mutations in NGF) share several similarities.…”
Section: Ikap Cellular Functions: Implications For Pns Deficitsmentioning
confidence: 60%
“…Furthermore, restoration of actin network function could improve neuronal survival, because actin dynamics mediate vesicle transport and are required specifically for the TrkA/NGF endosomal retrograde survival signaling in DRG neurons (53) that is necessary to prevent the default apoptotic response (46). Previous studies have suggested a role of IKAP/ELP1 in neuronal transport (36,54), and recent work has revealed that the speed of NGF retrograde transport is reduced in neurons lacking Ikbkap (40). Additionally, Rac-1, which interacts with actin to regulate growth cone dynamics (55), has been demonstrated in mammalian cells to be a target of BGP-15 treatment (31,32) and potentially could contribute to the positive effects of BGP-15 on the actin cytoskeleton, because actin has been shown to activate signaling cascades that lead to apoptosis (56).…”
Section: Discussionmentioning
confidence: 99%
“…One outstanding question is the physiological mechanisms mediating the erratic, elevated levels of dopamine in FD patient plasma that trigger the vomiting crises during “autonomic storms” [70]. Studies in yeast have shown that IKAP negatively regulates exocytosis [20], and evidence has been provided for IKAP localization to synaptic vesicles [24] raising the testable question of whether aberrant regulation of synaptic transmission may explain some of the autonomic dysfunction in FD. Another question that can be addressed with these animal and cellular models are the underlying metabolic problems experienced by FD patients and recapitulated in mice: patients have a significantly decreased body mass index (BMI), and multiple studies on FD mouse models report weight reductions of 60–70% in mutant mice with an absence of white adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their pluripotent nature, stem cells can be differentiated into neuronal cells, thereby providing a powerful system for modeling human diseases in vitro . FD human embryonic stem cell (hESC) or induced pluripotent stem cell (iPSC)-derived peripheral nervous system progenitor cells (neural crest) and neurons have been generated and can serve as a potential tool to investigate the molecular mechanisms mediating the demise of neurons in FD [24, 6164]. In addition, the feasibility of large-scale small molecule screening using FD-iPSCs [62] has facilitated the discovery of potential therapeutic compounds that can increase splicing of the mutated IKBKAP mRNA in FD-patient iPSC-derived neural crest cells, and increase expression of genes that regulate the differentiation of sympathetic neurons such as ASCL1 and SCG10 .…”
Section: Stem Cell Models Of Familial Dysautonomiamentioning
confidence: 99%